A system for research data governance - Chua, Chiah Soon (Nanyang Technological University, 2022)
Researchers often experience the need to share data for collaboration purposes or to receive due credit. Dataverse is an existing solution used by numerous academic institutions for that but does not offer many security-related features. Hence, we propose DataGovernR, an extension tool for Dataverse, that provides commonly needed features like file encryption, quorum-based key sharing, and time-stamped cryptographic proof of upload. We explain the cryptographic primitives used, and describe, in detail, the design and implementation of DataGovernR as a Proof-Of-Concept application. Lastly, we offer some suggestions for future features of DataGovernR.